+0

0
279
1 \

Feb 1, 2019

#1
+1

For f-1(-3)    we have that either

2 - x  = -3                        or                                      2x - x^2 = -3

x = 5                                                                          x^2 - 2x - 3 = 0

not defined  for 2 - x                                                  (x - 3) ( x + 1) = 0

x = 3   or x = -1

only the first value is defined for 2x - x^2

For f-1(0)   we have that either

2 - x = 0                         or                                       2x - x^2 = 0

x = 2- 0                                                                      x^2 - 2x = 0

x = 2                                                                          x(x - 2) = 0

not defined for    2 - x                                                x = 0   or x = 2

only the second value is defined for 2x - x^2

For f-1(3)  we have that either

2 - x = 3

x = 2 -3

x = -1

This is defined for 2 - x

So

f-1(-3) + f-1(0) + f-1(3) =

3  + 2   - 1   =

4   Feb 1, 2019